Castle Oaks Learning Portfolio: How we stand tall to end injustices and become allies to walk the path of Truth and Reconciliation

(untitled) (First Nations Child and Family Caring Society of Canada, 2024)
Students in F3A, F4A, 34A, F45, F5A and F5B at Castle Oaks Public School are learning how to stand tall and how to use their voices to advocate for equitable services and resources for Indigenous children. We are learning how we can listen, learn and honour the Truth in order to be allies and walk the path of Reconciliation. With our Reconciliation Ambearristers, we are learning how we can stand tall to end inequities and create a fair, safe and caring world for all children. We created a learning portfolio to showcase our learning thus far.